1986
DOI: 10.1002/jcp.1041260310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amino acid levels on matrix vesicle formation by epiphyseal growth plate chondrocytes in primary culture

Abstract: The effect of varying the amino acid concentrations of the culture medium on matrix vesicle formation was studied in primary cultures of chicken epiphyseal growth plate chondrocytes grown in Dulbecco's modified Eagle's medium (DME) supplemented with 10% fetal bovine serum (FBS). Decreasing the levels of free amino acids in the culture medium to levels of one-half, one quarter, and one eighth of the values normally present in DME caused a progressive decline in matrix vesicle (MV) formation. Increasing the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In summary, this study revealed that the level of specific AAs in the cartilage ECF is not only critical for the growth of the chondrocytes, but also it is important for the formation of MV [70]. However, the local environment of cells in vivo varies significantly from cell to cell; therefore, this finding cannot be generalized to all cell types, and further studies are required to determine the composition of media in which the response of various cell types can be achieved [70]. AA intake can also increase bone mineral density (BMD) by increasing insulin-like growth factor 1 (IGF-1), which is involved in osteoblastic activity and the synthesis of collagen and muscle proteins [72].…”
Section: Effect Of Amino Acids On Mineralization In Vivomentioning
confidence: 68%
See 1 more Smart Citation
“…In summary, this study revealed that the level of specific AAs in the cartilage ECF is not only critical for the growth of the chondrocytes, but also it is important for the formation of MV [70]. However, the local environment of cells in vivo varies significantly from cell to cell; therefore, this finding cannot be generalized to all cell types, and further studies are required to determine the composition of media in which the response of various cell types can be achieved [70]. AA intake can also increase bone mineral density (BMD) by increasing insulin-like growth factor 1 (IGF-1), which is involved in osteoblastic activity and the synthesis of collagen and muscle proteins [72].…”
Section: Effect Of Amino Acids On Mineralization In Vivomentioning
confidence: 68%
“…More specifically, they showed that the concentrations of charged AAs, such as Arg, Asp and Glu, which are strongly involved in mineralization, were 0.44, 3.76 and 15.37 mM in chicken hypertophic cartilage extracellular fluid (ECF), whereas it was 0.37, 0.06 and 0.16 mM, respectively, in blood plasma [69]. They also revealed that increasing the concentration of eight AAs (Asp, Glu, Ser, Gly, Ala, Pro, taurine (Tau), and asparagine (Asn)) in the culture medium to the level present in the native cartilage ECF remarkably stimulated the formation of alkaline phosphatase (AP) and AP-rich matrix vesicles (MV) by chondrocytes [70]. Among these AAs, Pro and Gly showed the weakest effect on AP production while the combination of only two of the AAs, Ala and Glu, produced stimulatory effect on MV formation comparable to that seen in the presence of the eight AAs.…”
Section: Effect Of Amino Acids On Mineralization In Vivomentioning
confidence: 94%
“…This culture medium, DATP5, fully supports proliferation, differentiation, and mineralization of primary cultures of GP chondrocytes isolated from rapidly growing broiler-strain chickens [Ishikawa et al, 1986;Wu et al, 1989Wu et al, , 1995Ishikawa and Wuthier, 1992]. Of special importance are supplemental ascorbate [Wu et al, 1989], specific amino acids [Ishikawa et al, 1986], and inorganic phosphate [Ishikawa and Wuthier, 1992], although other factors present in serum are also known to be important. This serum-containing medium consistently supports calcification in the absence of organic phosphate supplements.…”
mentioning
confidence: 98%
“…The culture media were changed every 3-4 days with a fresh supplement of ascorbic acid (50 mg/ml) starting on day 3, for the duration of the experiments. The medium was later changed to DATP5 mineralization medium (Ishikawa et al, 1997), which is enriched with eight amino acids to levels normally present in growth plate extracellular fluid (Ishikawa et al, 1985(Ishikawa et al, , 1986, and contains insulin (5 mg/ml), transferrin (5 mg/ml), sodium selenite (5 ng/ ml), 5% defined FBS, and 1 mM Na 2 HPO 4 added to the DMEM basal medium . In this culture medium, inorganic phosphate (Pi) is also raised to the level present in normal growth plate extracellular fluid, which enables mineral formation.…”
Section: Methodsmentioning
confidence: 99%
“…2). The DATP5 medium used for these cells was designed to mimic the electrolyte (Wuthier, 1977) and amino acid (Ishikawa et al, 1985;Ishikawa et al, 1986) composition of normal growth plate extracellular fluid. We had used it extensively for Osteogenic protein-1 (OP-1) was administered at 15 ng/dish (2 ml of culture medium).…”
Section: 2000; Farquharson and Jefferies 2000)mentioning
confidence: 99%